STRENGTHENING THE ECONOMY OF SMALL-SCALE FISHERMEN: THE ROLE OF ENTREPRENEURIAL MARKETING PROCESSES IN ENHANCING FINANCIAL PERFORMANCE TO REDUCE POVERTY - Efani A.; Sari M.; Utami T.N.; Putra A.T. (Russian Journal of Agricultural and Socio-Economic Sciences)
Small-scale fishermen on the southern coast of Java face various challenges, including structural poverty, limited market access, and low understanding of financial management and digital marketing. Additionally, they are affected by climate change, which has led to decreased catch yields and heightened safety risks. A lack of innovation in processing their catch and limitations in marketing strategies further exacerbate their economic conditions. This study aims to analyze the implementation of Entrepreneurial Marketing Processes (EMP) as an approach to enhance the welfare and reduce poverty among small-scale fishermen by improving the financial performance of fishing communities. Using Partial Least Square-Structural Equation Modeling (PLS-SEM), the study evaluates the effects of reputation, cost advantage, differentiation, innovation, and financial performance of small-scale fishermen, involving 100 small-scale fishermen respondents. The findings show that innovation and corporate reputation significantly influence cost advantage and product differentiation, which ultimately improve the financial performance of fishermen. The implementation of EMP has proven effective in helping small-scale fishermen maximize market opportunities, increase efficiency, and create value-added products. The resulting policy recommendations are expected to assist in the development of poverty alleviation programs focused on empowering fishermen through innovative and sustainable marketing strategies.